Sovereignty Mismatch and the New Administrative Law - David Zaring (Washington University Law Review, 2013)
In the United States, making international policymaking work with domestic administrative law poses one of the thorniest of modern legal problems—the problem of sovereignty mismatch. Purely domestic regulation, which is a bureaucratic exercise of sovereignty, cannot solve the most challenging issues that regulators now face, and so agencies have started cooperating with their foreign counterparts, which is a negotiated form of sovereignty. But the way they cooperate threatens to undermine all of the values that domestic administrative law, especially its American variant, stands for. International and domestic regulation differ in almost every important way: procedural requirements, substantive remits, method of legitimation, and even in basic policy goals. Even worse, the delegation of power away from the United States is something that our constitutional, international, and administrative law traditions all look upon with great suspicion. The resulting effort to merge international and domestic regulatory styles has been uneven at best. As the globalization of policymaking is the likely future of environmental, business conduct, and consumer protection regulation—and the new paradigm-setting present of financial regulation—the sovereignty mismatch problem must be addressed; this Article shows how Congress can do so.
Keywords: sovereignty; administrative law; policymaking; globalization